2021
DOI: 10.1192/bjo.2021.1047
|View full text |Cite
|
Sign up to set email alerts
|

Young age and the risk of violent behaviour in people with severe mental disorders: prospective, multicentre study

Abstract: Background During adolescence and young adulthood people appear to be more prone to violent behaviour. A greater tendency to violent behaviour appears to be associated with hyperactivity, impulsivity and low tolerance for frustration and provocation in social settings. Aims This prospective cohort study aimed to evaluate rates of violent behaviour among young people with mental disorders, compared with older age groups. Method A total of 340 individuals with severe ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…In terms of predictors of aggression, patients with certain demographic and social characteristics were more prone to aggression. The findings in this review were congruent with previous findings which included younger age [37][38][39][40][41][42], older age [43], being unmarried [38,[44][45][46], being childless [47], lower education [44], unemployment [44,[48][49][50], lower intelligence [38], financial issues [51,52] and homelessness [53]. Of note, an earlier study found an association between homelessness and crimes, but not specifically aggressive crimes [54].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of predictors of aggression, patients with certain demographic and social characteristics were more prone to aggression. The findings in this review were congruent with previous findings which included younger age [37][38][39][40][41][42], older age [43], being unmarried [38,[44][45][46], being childless [47], lower education [44], unemployment [44,[48][49][50], lower intelligence [38], financial issues [51,52] and homelessness [53]. Of note, an earlier study found an association between homelessness and crimes, but not specifically aggressive crimes [54].…”
Section: Discussionsupporting
confidence: 90%
“…Another difficulty for the clinician is to conceptualise the client's aggressiveness in the absence of a framework to guide the assessment of aggression in a systematic and comprehensive manner. While there are instruments for assessing dangerousness in people with severe mental disorders (Hodgins et al, 2003;Micciolo et al, 2021), risk of recidivism in correctional settings (Desmarais et al, 2016;Olver et al, 2022), and severe behavioural disorders in people with intellectual disabilities or autism spectrum disorders (Hastings et al, 2021;Hemmings et al, 2008;Hill et al, 2014), these methods are not always adapted to the clientele seen in private office, outpatient clinics, and hospitals. Knowing when and how to assess aggressive behaviours is essential to avoid the negative consequences of not conducting an assessment or of conducting it hastily, and not planning interventions that address each of the possible causes of aggression and thus maximise the chances of therapeutic success.…”
Section: Aggressive Behaviour In Clinical Settingsmentioning
confidence: 99%
“…A meta-regression analysis of risk factors for VB in psychosis (EPP or chronic patients) found that, among several dynamic psychopathological risk factors, high impulsivity was an important one ( 34 , 35 ). Several studies have shown the impact of impulsivity on VB with different populations [chronic patients ( 34 36 , 84 , 85 ), EEP patients ( 37 , 50 , 86 ), and forensic populations ( 85 )] and different measures of impulsivity (clinical self-report or hetero-report and behavioral scales) ( 73 , 86 88 ). In the EEP, prospective cohort studies have also shown that impulsivity is associated with serious aggression ( 37 , 50 ), either directly or indirectly.…”
Section: Role Of Impulsivity In the Relationship Between Cannabis Use...mentioning
confidence: 99%